(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This paper explores the relationship between complex numbers and analytical functions. Complex numbers consist of real and imaginary parts and are widely used in various fields of mathematics. Analytic functions are crucial when working with complex variables. These functions are based on the Cauchy-Riemann equations, which define their properties in a given domain. The study examines the key concepts of complex functions, their differentiability, and analytical properties.